Management of Khidmah Practices at Mualimin Muadalah Islamic Boarding Schools to Produce Quality Graduates - Dzakiyyuddin, Mohammad; Sanusi, Achmad; Wahidin, Didin; Saeful Insan, Husen (International Journal of Educational Research & Social Sciences, 2022)
The purpose of this study is to investigate and reveal the management process carried out in the khidmah practice of Mualimin Muadalah Pesantren as a tradition as well as a unic programme to produce quality graduates. This study was conducted at two Mualimin Muadalah Pesantren of West Java Province, namely Pesantren Darussalam Garut and Pesantren Fajrussalam Bogor. The method used is qualitative research with descriptive analysis techniques. The data is based on observation, interviews, and documentation records. Research findings reveal that the participants undergo one year of preparatory training in scientific writing, Islamic ancient scripture literacy, worship leadership, teaching skills, and Arabic and English language skills. The training was satisfies the institution although its stopped early due to the outbreak of the Covid19 pandemic. After training, participants were sent to undergo a one-year field service period consists of two domains: (1) carrying out teaching and administrative duties; (2) working in the organizational structure of the pesantren and being involved in social and religious events held by the pesantren. The management of teacher service practice does not show significant problems, while the management of boarding service practice is still constrained by inconsistency in supervision and assessment system that is not yet optimal.